The internet, political mobilisation and civic engagement in Zimbabwe from 2015 to 2020: investigating the role of Twitter - Pindayi, Brian (Centre for Film and Media Studies, 2022)
This study sought to determine how Twitter affected political mobilisation and civic engagement in Zimbabwe from 2015 to 2020. Zimbabwe's competitive authoritarian regime has over the years restricted access to mainstream media platforms, leaving members of the opposition and most civic organisations with no recourse but to resort to social media platforms such as Twitter for purposes of political mobilisation and civic engagement. The research questions were: How did Zimbabwean political actors, namely ZANU-PF, MDC formations, Build Zimbabwe, National People's Party, Independent candidates and ordinary citizens use Twitter for political engagement from 2015 to 2020? To what extent has Twitter influenced political mobilisation in Zimbabwe from 2015 to 2020? What examples are there of successful civic engagement through Twitter in Zimbabwe from 2015 to 2020? A thematic analysis of tweets from political parties that contested the 2018 elections, politicians, civic organisations and private citizens was carried out. Eight themes were identified, four measuring political mobilisation and four measuring civic engagement. For political mobilisation the themes were, engaging ZANU-PF, engaging MDC Alliance, sanctions, and corruption. For civic engagement the themes were focusing on humanitarian aid or causes, personal exchanges, provocative or gaslighting tweets, and human rights or legal issues. Findings indicate that Twitter, has several affordances that result in socio-political influences. Twitter empowers opposition parties and citizens in Zimbabwe. It constitutes a collaborative space on which different political parties pursue common objectives. The accumulation of information and conversations makes Twitter a historical database with verification capabilities. Furthermore, as Zimbabweans have been using Twitter to connect with specific issues and online communities, it has served as an endorsement and/or verification platform. The multiplicity of voices and opinions have made Twitter a marketplace of ideas. By enabling certain individuals or issues to gain prominence, Twitter has become a snowball amplifier of events and issues. Twitter creates boundless, extended or international communities as political actors and citizens across international boundaries have centralised or focused debates. Several opposition politicians, civic organisations and citizens have relied on Twitter to spread information and influence mainstream media channels in what exemplifies a phenomenal ‘Twitter effect'. The political persecution, lawfare and suspension of Twitter accounts has demonstrated how Twitter can be an ephemeral, mutating and transient platform. These metaphoric categories all demonstrate how Twitter serves as an alternative public sphere in Zimbabwe, a potent forum for subaltern counter publics.